Pelvic inflammatory disease - Ross, Jonathan D C (BMJ Publishing Group, 2008)
INTRODUCTION: Pelvic inflammatory disease is caused by infection of the upper female genital tract and is often asymptomatic. Pelvic inflammatory disease is the most common gynaecological reason for admission to hospital in the USA and is diagnosed in almost 2% of women aged 16 to 45 years consulting their GP in England and Wales. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of empirical treatment compared with treatment delayed until the results of microbiological investigations are known? How do different antimicrobial regimens compare? What are the effects of routine antibiotic prophylaxis to prevent pelvic inflammatory disease before intrauterine contraceptive device (IUD) insertion? We searched: Medline, Embase, The Cochrane Library, and other important databases up to May 2007 (Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found nine systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review, we present information relating to the effectiveness and safety of the following interventions: antibiotics (oral, parenteral, empirical treatment, treatment guided by test results, different durations, outpatient, inpatient), and routine antibiotic prophylaxis (before intrauterine device insertion in women at high risk or low risk).